Regulation of IRES-mediated translation in p53 - Fonseca Costa, Inês (2020)
The tumor microenvironment is characterized by several stresses impairing canonical translation. However, specific mRNAs harbouring internal ribosome entry sites (IRES), such as several tumour suppressors and oncogenes, can overcome this impairment. The tumor suppressor TP53 gene, an important transcription factor that ensures cellular homeostasis, is frequently mutated in human cancers. Over the years, several p53 isoforms have been identified, which in some cases result from alternative initiation of translation regulated by an IRES. Recently, we have associated mutant p53 “gain-of-function” cancer phenotype, such as enhanced cell survival, invasion, proliferation, and adhesion, with the expression of higher levels of shorter p53 isoforms, such as Δ160p53 isoform.1 Here, we used a bicistronic system containing two reporter luciferases (renilla luciferase and firefly luciferase) to assess IRES-mediated translation. Several p53 mRNA elements were tested in this system and, interestingly, we have found an inhibitory element of IRES-mediated translation. Overall, IRES-regulated translation in malignant cells is used to translate specific proteins that promote cancer progression. Thus, inhibiting translation of oncogenes via IRES could prevent the formation of tumor cells and their adaptation to unfavourable conditions in the tumor microenvironment. 1. Candeias, M. M., Hagiwara, M. & Matsuda, M. Cancer‐specific mutations in p53 induce the translation of Δ160p53 promoting tumorigenesis. EMBO Rep. 17, 1542–1551 (2016).